Prokineticin 2 neurons form diverse subpopulations in the suprachiasmatic nucleus and rely on VPAC2-signaling for diurnal rhythmicity - Stangerup, Ida; Georg, Birgitte; Hannibal, Jens (Frontiers in Physiology, 2025)
IntroductionProkineticin 2 (PK2) is believed to function as an output molecule, relaying circadian rhythms of behavior and physiology from the suprachiasmatic nucleus (SCN). The expression of PK2 in the SCN is primarily driven by the molecular clock, oscillating with high levels early-mid day and low levels during night. Furthermore, light at night induces the expression of PK2. Until recently, the absence of a reliable PK2 antibody has hindered characterization of PK2 neurons in the SCN, including whether they constitute a phenotypically homogeneous population or comprise distinct subtypes, some potentially light-responsive. Hence, the aim of this study was to characterize PK2 neurons in relations to light-responsiveness and neuropeptidergic markers of the core-shell division.MethodsDouble and triple immunohistochemistry of PK2 together with phenotypical neuropeptide/receptor markers of the core-shell division was performed at zeitgeber time (ZT) 8. Light-responsiveness of PK2 SCN neurons was evaluated using FOS and EGR1 ZT18, 2 h following a 30-min light-pulse stimulation. Data were visualized and processed using confocal microscopy. Moreover, PK2 mRNA was evaluated over a 12:12 light-dark cycle in both wildtype and VIP type 2 receptor (VPAC2) knockouts mice, using qPCR.ResultsThe majority of PK2 neurons were located in the shell, constituting a subpopulation of vasopressin (AVP) and neuromedin S (NMS) neurons. Few PK2 neurons were found in the ventral core, constituting a subpopulation of vasoactive intestinal polypeptide (VIP) and NMS neurons. PK2 shell neurons expressed the VPAC2 receptor, and in its absence, diurnal rhythmicity of PK2 mRNA was abolished. In addition, the PAC1 receptor—specific for pituitary adenylate cyclase-activating polypeptide (PACAP), one of two neurotransmitters of the retinohypothalamic tract—was found on some PK2 neurons. Moreover, nighttime light-pulse stimulation broadly induced FOS and EGR1 immunoreactivity throughout the SCN but only in few PK2 neurons.ConclusionPK2 SCN neurons are heterogeneous yet highly dependent on intact VIP-VPAC2 signaling to maintain a coherent diurnal expression pattern. A neuroanatomical and functional basis suggest two potential pathways for regulating PK2 expression: a diurnal mechanism involving VIP signaling through the VPAC2 receptor and a direct light-mediated pathway via retinal innervation through the PAC1 receptor.